2012
DOI: 10.1007/s13206-012-6303-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative lateral-flow immunoassay for the assessment of the cartilage oligomeric matrix protein as a marker of osteoarthritis

Abstract: This study reports a simple and quantitative analytical method for detecting cartilage oligomeric matrix protein (COMP) using a lateral-flow immunoassay (LFI) format. An immuno-chromatographic assay was developed using a gold nanoparticle (AuNP)-conjugated monoclonal antibody (Ab) probe for the quantitative detection of COMP in human synovial fluid (SF). The detection antibody was conjugated with the AuNP (~30 nm) to enable detection, and the capture antibody was immobilized within a multi-spot pattern in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…In the work of Hong et al (2012) the antibodies were dispensed as patterns of parallel and zigzag dots on the detection pad, being the zigzag pattern the one which gave the highest intensities, presumably being flow slower on this design. Recently, it has been demonstrated that wax is a useful tool due its hydrophobicity to control flow on paper devices and create channels on it (Renault et al, 2014).…”
Section: Enhancement Strategiesmentioning
confidence: 99%
“…In the work of Hong et al (2012) the antibodies were dispensed as patterns of parallel and zigzag dots on the detection pad, being the zigzag pattern the one which gave the highest intensities, presumably being flow slower on this design. Recently, it has been demonstrated that wax is a useful tool due its hydrophobicity to control flow on paper devices and create channels on it (Renault et al, 2014).…”
Section: Enhancement Strategiesmentioning
confidence: 99%
“…For instance, a quantitative lateral-flow immunoassay technique with antibodies conjugated to gold nanoparticles was used for the detection of COMP in the synovial fluid. The proposed method showed similar results to corresponding ELISA, with an average difference of <7% without the need of expensive equipment or complex procedures (127). However, most of the reported studies have investigated the use of advanced nanomaterial-enhanced immunoassays toward inflammatory biochemical markers.…”
Section: Nanotechnology Strategies To Enhance Selectivity and Sensitimentioning
confidence: 68%
“…The 20 nm AuNPs were synthesized according to the procedure described in previous reports [ 32 , 33 ]. The size of the AuNPs was determined with an ultraviolet–visible (UV–vis) spectrophotometer by scanning from 300 to 800 nm ( Figure S1A, Supporting information ) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The distributed spots allow for the quantitative analysis of an LFI with the naked eye. However, the accumulated immunocomplexes on the spots could affect the flow on the strip because of their large components, such as antigens, antibodies, and AuNPs [33]. The color development of the spot is not only determined by the concentration of antigens but also by the contact chance between the flow and spot.…”
Section: Effect Of Spot-pattern Alterations On the Signal Developmentmentioning
confidence: 99%